Influence of different polymeric materials of implant and attachment on stress distribution in implant-supported overdentures: a three-dimensional finite element study - Sherif Elsayed; Yousra Ahmed; Mohamed I. El-Anwar; Enas Elddamony; Reem Ashraf (BMC Oral Health)
Abstract Purpose Investigating high performance thermoplastic polymers as substitutes to titanium alloy, in fabrication of implants and attachments to support mandibular overdenture, aiming to overcome stress shielding effect of titanium alloy implants. Aim of study Assessment of stress distribution in polymeric prosthetic components and bone around polymeric implants, in case of implant-supported mandibular overdenture. Materials and methods 3D finite element model was established for mandibular overdenture, supported bilaterally by two implants at canine region, and retained by two ball attachments. Linear static stress analysis was carried out by ANSYS 2020 R1. Three identical models were created with different materials for modeling of prosthetic components (implant body, gingival former, ball attachment and matrix). The Monolithic principle was applied as the same material was used in modelling all the prosthetic components in each model (Titanium alloy grade V, poly-ether-ether-ketone (PEEK) and poly-ether-ketone-ketone (PEKK)). Simultaneous Force application of 60 N was carried out bilaterally at the first molar occlusal surface area using 3 runs (vertical, lateral and oblique). Results PEEK and PEKK prosthetic components exhibited the highest total deformation and critical Maximum von Mises stresses values in implant body and gingival former under lateral and oblique loads. The stress values approached the fatigue limit of both polymeric materials presenting low factor of safety (< 1.5). The Peri-implant cortical bone in case of PEEK and PEKK showed nearly double maximum principal stresses compared with the titanium model. Conversely, Maximum von Mises stresses in spongy bone were lower in polymeric models than those of titanium ones. Additionally maximum equivalent strain values in spongy peri-implant bone of polymeric models were also lower than those of titanium model. Conclusion Critical high stresses were induced in implant body and gingival former under oblique or lateral loadings, accordingly, fatigue failure of both PEEK and PEKK polymer prosthetic elements was estimated due to low factor of safety. Both PEEK and PEKK Polymer models offered no advantage over titanium one regarding stress shielding effect, due to low stress and strain values generated at spongy peri-implant bone in polymer models.